Optical electromotive microscale with first type Schrodinger frame - Korpinar, Talat; Korpinar, Zeliha; Asil, Vedat (Elsevier Gmbh, 2023)
In this paper, we define the first frame associated with the non-linear Schrodinger system. Also, we present Lorentz force in the first type of the non-linear Schrodinger frame associated with the Bishop frame in the Minkowski 3-space. We can define timelike pseudo-solitonic first class NCS electromotive microscale. Hence, we design first class NCS optical optimistic pseudo-solitonic density. Finally, we obtain electroosmotic solitonic NCS electromotive microscale is modeled by the first type of the non-linear Schrodinger frame vectors.
Keywords: Optical Schr?dinger frame; Antiferromagnetic microscale; Pseudo-solitonic density; Complex electromotive microscale